2009
DOI: 10.3181/0806-rm-184
|View full text |Cite
|
Sign up to set email alerts
|

Pyrin and ASC Co-Localize to Cellular Sites that Are Rich in Polymerizing Actin

Abstract: Familial Mediterranean fever (FMF) is an autoinflammatory disease caused by mutations in the MEFV locus, which encodes the protein pyrin. While it is known that pyrin is expressed in myeloid cells and several fibroblastic cell types, the exact function of pyrin in these cells and the mechanism underlying the pathological effect of pyrin mutations have yet to be revealed. Here, we document that in migrating human monocytes, pyrin protein is dramatically polarized at the leading edge, where it co-localizes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 36 publications
1
59
1
1
Order By: Relevance
“…These studies revealed that pyrin exists as a homotrimer in unstimulated cells and that stimulation releases an autoinhibitory interaction between the N terminal SPRY domain of pyrin and its B box. This now frees the SPRY domain of pyrin to facilitate interaction with ASC and thus promote activation of the inflammasome [94]. These studies concur with the phenotype of mice expressing the pyrin domain alone which show enhanced IL-1β processing, whereas full length pyrin inhibits these responses.…”
Section: Autoinflammatory Diseases -Inflammasome Regulation By Trim Fsupporting
confidence: 75%
See 1 more Smart Citation
“…These studies revealed that pyrin exists as a homotrimer in unstimulated cells and that stimulation releases an autoinhibitory interaction between the N terminal SPRY domain of pyrin and its B box. This now frees the SPRY domain of pyrin to facilitate interaction with ASC and thus promote activation of the inflammasome [94]. These studies concur with the phenotype of mice expressing the pyrin domain alone which show enhanced IL-1β processing, whereas full length pyrin inhibits these responses.…”
Section: Autoinflammatory Diseases -Inflammasome Regulation By Trim Fsupporting
confidence: 75%
“…Inflammatory stimuli results in the release of an autoinhibitory interaction between pyrins N terminal SPRY domain and its B box domain. Once activated, the SPRY domain then interacts with ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain) promoting its oligomerisation and activation of the inflammasome [94,112].…”
Section: Figure Legendsmentioning
confidence: 99%
“…Subsequent work showed that this protein formed an inflammasome complex for the activation of IL-1 and IL-18 and that it is also an actin-binding protein (Mansfield et al, 2001;Richards et al, 2001;Waite et al, 2009). We now show that a lack of actin depolymerization triggers the pyrin inflammasome in vivo, using a mouse model of autoinflammatory disease.…”
Section: Discussionmentioning
confidence: 87%
“…It is tempting to speculate that the trigger is some modified form of actin given that pyrin binds to, and colocalizes with, polymerizing actin (Mansfield et al, 2001;Richards et al, 2001;Waite et al, 2009). However, further work is required to investigate this interaction.…”
Section: Wdr1 Rd/rd M-csf-derived Cells Secrete Increased Il-18 In Rementioning
confidence: 99%
See 1 more Smart Citation